Effects of total parenteral nutrition on postnatal growth in very low birth weight and extremely low birth weight newborns - Ahuja, Divya; Srivastava, Pritosh; Srivastava, Anshuman (International Journal of Research in Medical Sciences, 2020)
Background: Prematurity is the most important cause of mortality in Under-5 children responsible for one million deaths/ year. Premature babies are not able to store enough nutrients for their optimal survival; it is essential to provide them total parenteral nutrition. Intravenous lipid infusion in neonates is linked with high risk of sepsis and thrombocytopenia. PN with amino acids and glucose can be imparted to achieve nutritional goal. This trial was intended to assess the effects of various components of amino acid PN on postnatal growth in VLBW and ELBW newborns. Methods: A prospective observational study was conducted from January 2018 - May 2019 in NICU of TMMC and RC which included preterm newborns with birth weight of less than 1500gms who received aminoven infusion. Anthropometric measurements, incidence of hypo/hypercalcaemia, hypo/hyperglycaemia, direct hyperbilirubinemia, incidence of sepsis were evaluated. Results: Out of 22 patients, 12 neonates received high dose aminoven therapy whereas 10 neonates received low dose aminoven therapy. It was seen that rapid rate of increment of amino acids had adequate weight on discharge, 72.72% have adequate growth among the rapid group compared to 36.36% among slower group. No significant changes in calcium metabolism or glucose metabolism were seen in both the groups. Conclusions: In resource limited settings, parenteral nutrition with intravenous amino acids have a better effect on the weight of preterm newborns at discharge when high doses of amino acids infusion started early with rapid increment in the dose.